Economy, Education and Physical Education in Kenya in the Light of Statistical Indicators - HIDEG Gabriella (Ученые записки Института Африки Российской академии наук)
Kenya was once a British colony, and today it is a fast-growing country with world-class hotels and shopping malls on one side of the road, while misery and poverty show their cruel faces on the other side. It is a country where internal struggles and political unrest are ongoing, corruption is enormous, and an increasing number of terrorist organizations are appearing (even breaking into universities and slaughtering young people for their religious affiliation).